The Influence of Sustainable Marketing on Gen Z Users' Value Perception, Image, and Intention at Sports Events - Baswara, Satsya Yoga; Widhiastuti, Ratieh; Rahayu, Tandiyo; Dewi, Eko Nurcahya; Saefullah, Muhamad Rekhan; Ni’am, Sufa’Ah Hurumun (Economic Education Analysis Journal, 2024)
The recent upsurge in sporting events has instigated a positive shift in the habits of Generation Z, placing a strong emphasis on embracing a healthy lifestyle through sports while also prioritizing other aspects of life. This comprehensive study delves into the impact of sustainable marketing activities (SMA) on the perceived value and self-image associated with sporting events, as well as its influence on the intention of Gen Z individuals to actively participate in these events (Sports User Behavioral Intention/SUBI). Given the paramount importance of sustainability in organizing sporting events, this study aims to uncover effective strategies for marketing these events to appeal to a wider user base, both in digital and non-digital realms. Through comprehensive data collection via questionnaires and rigorous analysis using the PLS (Partial Least Squares) method, we anticipate elucidating the intricate relationship between SMA, sports event image, perceived value, and sports user intention. Additionally, we seek to explore the mediating role of perceived value and event description in this dynamic relationship. The results of this study hold the potential to revolutionize sustainable marketing for sports events and carry profound implications for event management and sustainability. By identifying limitations and opportunities for future research, this study paves the way for further advancements in this vital field.